La terapia immunosoppressiva nel trapianto di rene - Aris Tsalouchos; Maurizio Salvadori (AboutScience Srl, 2019)
Immunosuppressive therapy in renal transplantation can be distinguished in induction therapy and maintenance therapy. Induction therapy is an intense immunosuppressive therapy administered at the time of kidney transplantation to reduce the risk of acute allograft rejection. In general, the induction immunosuppressive strategies used at kidney transplant centers fall into one of these two categories. One strategy relies upon high doses of conventional immunosuppressive agents, while the other utilizes antibodies directed against T-cell antigens in combination with lower doses of conventional agents. Maintenance immunosuppressive therapy is administered to almost all kidney transplant recipients to help prevent acute rejection and loss of the renal allograft. Although an adequate level of immunosuppression is required to dampen the immune response to the allograft, the level of chronic immunosuppression is decreased over time (as the risk of acute rejection decreases) to help lower the overall risk of infection and malignancy; these risks directly correlate with the degree of overall immunosuppression. The optimal maintenance immunosuppressive therapy in kidney transplantation is not established. The major immunosuppressive agents that are available in various combination regimens are glucocorticoids (primarily oral prednisone), azathioprine, mycophenolate mofetil (MMF), enteric-coated mycophenolate sodium (EC-MPS), cyclosporine (in non-modified or modified [microemulsion] form), Tacrolimus, everolimus, rapamycin (sirolimus), and Belatacept.